In Situ Attenuated Total Reflectance Fourier‐Transform Infrared Study of Oxytetracycline Sorption on Magnetite. Issue 3 (1st May 2013) - Rakshit, Sudipta; Elzinga, Evert J.; Datta, Rupali; Sarkar, Dibyendu
Abstract : Adsorption of antibiotics on the surfaces of common mineral sorbents plays a major role in determining their fate in soils and sediments. The mechanisms of these reactions are, therefore, important for understanding and predicting the environmental fate of antibiotics. We used in situ attenuated total reflectance Fourier‐transform infrared spectroscopy to elucidate the binding mechanisms of oxytetracycline (OTC) onto the surface of magnetite [Fe3 O4(s) ], a common Fe oxide mineral in soils and sediments, as a function of pH (3–9) and aqueous OTC concentration (5–150 μmol L −1 ). Comparison of dissolved OTC spectra to those of OTC–magnetite surface complexes indicated strong interactions of OTC molecules with the Fe3 O4(s) surface via carbonyl (C=O) and amine (–NH2 ) moieties of the amide group (–CONH2 ) and the N atom of the dimethyl amino group [–N(CH3 )2 ]. Increasing the aqueous OTC concentration led to increased OTC adsorption but did not notably alter the OTC binding mode at the magnetite surface. The results of this study would help to assess the importance of Fe oxide minerals in determining the environmental fate of OTC in soils and sediments.